EXTRACTION MECHANIZATION OF SOFT SOILS - Ivanova, Polina; Ivanov, Sergey; Mikhailov, Aleksander; Shishlyannikov, Dmitriy (Journal of Applied Engineering Science, 2021)
The state economic development is largely determined by the effectiveness of its individual structural elements. Among them, a special place is occupied by trends in the mineral sector, which dictates the requirements and mechanisms for the development of natural resources, creating the basis for a national strategy. However in this area there are a number of unsolved problems, which include: a low level of rational use of machine-technological mining systems from under the water with minimal man-made impact. The authors consider existing and alternative extraction methods of peat raw materials. The tasks facing the mineral resource sector can be solved through technological priority developments of aggregated extraction complexes for the peat raw materials and the equipment modernization for mining complexes. The analysis is carried out and recommendations are made for the working equipment modernization of the aggregated mining complex. Variants of the excavator excavation bucket for the extraction of peat raw materials from under water have been proposed. The results of studies on primary dehydration, combining mining and dewatering cycles in a bucket, are presented; the work gives the recommendations on the bucket use and the expediency of operating the mining machine’s extraction body when extracting peat raw materials.